2019
DOI: 10.1088/2515-7647/ab2c84
|View full text |Cite
|
Sign up to set email alerts
|

Colour optimization of phosphor-converted flexible nitride nanowire white light emitting diodes

Abstract: We demonstrate flexible nanowire white light-emitting-diodes (LEDs) with an optimized colour quality. The devices consist of flexible InGaN/GaN nanowire LEDs acting as pumps, capped with removable phosphor-doped polydimethylsiloxane membranes. Five different phosphors with tens of microns in grain size emitting from green to orange are investigated using both violet-blue and a bluegreen nanowire-based LED pumps. In addition, a flexible nanowire white LED with a warm white emission is demonstrated using two lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The first flexible phosphor-converted white microrod LED is depicted in Figure 7 e; it had a CCT of 6306 K, a CRI of 54, and an EQE of 9.3%. The CRI was later improved to a value of 65 by using two layers of yellow and orange phosphors [ 4 ].…”
Section: Application Of Ingan/gan Core–shell Microrod Ledsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first flexible phosphor-converted white microrod LED is depicted in Figure 7 e; it had a CCT of 6306 K, a CRI of 54, and an EQE of 9.3%. The CRI was later improved to a value of 65 by using two layers of yellow and orange phosphors [ 4 ].…”
Section: Application Of Ingan/gan Core–shell Microrod Ledsmentioning
confidence: 99%
“…The unique three-dimensional (3D) architecture promises novel properties that may be attractive for solid-state lighting or even open further application fields of GaN-based LEDs. These include (flexible) white LEDs [ 3 , 4 ], single-photon sources [ 5 ], and high-frequency LEDs [ 1 , 6 ]. Microrod LEDs have a high surface-to-volume ratio, creating an enlarged light output area for the same chip size [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Kubelka-Munk (K-M) equation was used to calculate the absorption spectra for SLPO from its scattered spectra in order to experimentally determine the SLPO compound optic bandspace magnitude [24], which is expressed as (1). The Tauc connection links the bandgap E g and α with the straight absorption coefficient of a substance [25], as used in (2).…”
Section: Luminous Characteristics and Energy Transmission In Slpo:ce ...mentioning
confidence: 99%
“…[ 22–25 ] Nanowire‐based LEDs with blue core/shell InGaN/GaN MQWs combined with phosphors reach measured external quantum efficiency as high as 9% for white light emission. [ 26–28 ] Core–shell InGaN/GaN heterostructures can also exhibit multicolor emission related to different indium incorporation on specific crystallographic facets and edges. [ 29–31 ] For instance, Choi et al reported orthogonally polarized dual‐wavelength emission from InGaN/GaN core–shell microrod arrays due to different indium content in the m ‐plane facets compared with the edges leading to spatially separated blue and green emissions.…”
Section: Introductionmentioning
confidence: 99%